Gut bacterial ClpB-like gene function is associated with decreased body weight and a characteristic microbiota profile - Arnoriaga-Rodríguez, María; Mayneris-Perxachs, Jordi; Burokas, Aurelijus; Pérez-Brocal, Vicente; Moya, Andrés; Portero-Otin, Manuel; Ricart, Wifredo; Maldonado, Rafael; Fernández-Real, José-Manuel (Microbiome, 2020)
Background The chaperone ClpB, a bacterial protein, is a conformational antigen-mimetic of α-melanocyte-stimulating hormone (α-MSH) implicated in body weight regulation in mice. We here investigated the potential associations of gut bacterial ClpB-like gene function with obesity status and gut microbiota in humans. Results Gut microbiota ClpB KEGG function was negatively associated with body mass index, waist circumference, and total fat mass (DEXA). The relative abundance (RA) of several phyla and families directly associated with ClpB was decreased in subjects with obesity. Specifically, the RA of Rikenellaceae , Clostridiaceae and not assigned Firmicutes were lower in subjects with obesity and positively associated with gut bacterial ClpB-like gene function (not assigned Firmicutes ( r = 0.405, FDR = 2.93 × 10−2), Rikenellaceae ( r = 0.217, FDR = 0.031), and Clostridiaceae ( r = 0.239, FDR = 0.017)). The gut bacterial ClpB-like gene function was also linked to specific plasma metabolites (hippuric acid and 3-indolepropionic acid) and fecal lupeol. The α-MSH-like epitope similar to that of Escherichia coli ClpB was also identified in some sequences of those bacterial families. After fecal transplantation from humans to mice, the families that more contributed to ClpB-like gene function in humans were also associated with ClpB-like gene function in mice after adjusting for the donor’s body mass index (not assigned Firmicutes ( r = 0.621, p = 0.003), Prevotellaceae ( r = 0.725, p = 4.1 × 10 −7 ), Rikenellaceae ( r = 0.702, p = 3.9 × 10 −4 ), and Ruminococcaceae ( r = 0.526, p = 0.014)). Clostridiaceae ( r = − 0.445, p = 0.038) and Prevotellaceae RA ( r = − 0.479, p = 0.024) and were also negatively associated with weight gain in mice. The absolute abundance (AA) of Prevotellaceae in mice was also positively associated with the gut bacterial ClpB-like gene function in mice. DESeq2 identified species of Prevotellaceae , both negatively associated with mice’ weight gain and positively with gut bacterial ClpB-like gene function. Conclusions In summary, gut bacterial ClpB-like gene function is associated with obesity status, a specific gut microbiota composition and a plasma metabolomics profile in humans that could be partially transplanted to mice. 9EgaQCzZBK_kpa4vXvXSr4 Video Abstract